Formation of a Stable Co-Amorphous System for a Brick Dust Molecule by Utilizing Sodium Taurocholate with High Glass Transition Temperature - Shohei Aikawa; Hironori Tanaka; Hiroshi Ueda; Masato Maruyama; Kazutaka Higaki (Pharmaceutics, 2022)
Brick dust molecules are usually poorly soluble in water and lipoidal components, making it difficult to formulate them in dosage forms that provide efficient pharmacological effects. A co-amorphous system is an effective strategy to resolve these issues. However, their glass transition temperatures (Tg) are relatively lower than those of polymeric amorphous solid dispersions, suggesting the instability of the co-amorphous system. This study aimed to formulate a stable co-amorphous system for brick dust molecules by utilizing sodium taurocholate (NaTC) with a higher Tg. A novel neuropeptide Y5 receptor antagonist (AntiY5R) and NaTC with Tg of 155 °C were used as the brick dust model and coformer, respectively. Ball milling formed a co-amorphous system for AntiY5R and NaTC (AntiY5R-NaTC) at various molar ratios. Deviation from the theoretical Tg value and peak shifts in Fourier-transform infrared spectroscopy indicated intermolecular interactions between AntiY5R and NaTC. AntiY5R-NaTC at equal molar ratios resulting in an 8.5-fold increase in AntiY5R solubility over its crystalline form. The co-amorphous system remained amorphous for 1 month at 25 °C and 40 °C. These results suggest that the co-amorphous system formed by utilizing NaTC as a coformer could stably maintain the amorphous state and enhance the solubility of brick dust molecules.